The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s00122-022-04122-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of epigenetic variation of crop wild relatives for crop improvement and agrobiodiversity preservation

Abstract: Crop wild relatives (CWRs) are recognized as the best potential source of traits for crop improvement. However, successful crop improvement using CWR relies on identifying variation in genes controlling desired traits in plant germplasms and subsequently incorporating them into cultivars. Epigenetic diversity may provide an additional layer of variation within CWR and can contribute novel epialleles for key traits for crop improvement. There is emerging evidence that epigenetic variants of functional and/or ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 173 publications
0
8
0
Order By: Relevance
“…Advances in the knowledge of epigenetic regulation in the plant multiple generation stress memory have provided new procedures and approaches for breeding crops and sustainable germplasm banks for future climate challenges [112,113]. Plant stress memory is described under two categories: mitotic stress memory, or somatic memory, and meiotic stress memory, or transgenerational memory [114][115][116]. Plant stress memory associated with the inheritance of SAR is likely to be epigenetic [117,118].…”
Section: Memory Of Plant Immunizationmentioning
confidence: 99%
“…Advances in the knowledge of epigenetic regulation in the plant multiple generation stress memory have provided new procedures and approaches for breeding crops and sustainable germplasm banks for future climate challenges [112,113]. Plant stress memory is described under two categories: mitotic stress memory, or somatic memory, and meiotic stress memory, or transgenerational memory [114][115][116]. Plant stress memory associated with the inheritance of SAR is likely to be epigenetic [117,118].…”
Section: Memory Of Plant Immunizationmentioning
confidence: 99%
“…In recent decades, emerging epigenetic processes have been highlighted as promising mechanisms to facilitate the generation of the first tier of rapid phenotypic diversity required to improve the fitness and adaptive responses in the natural populations of plants ( Bräutigam et al, 2013 ; Amaral et al, 2020 ; Ashe et al, 2021 ). A survey of published literature shows that a large number of research investigations wherein the epigenetic route has been shown to deploy rapid phenotypic plasticity for adaptation and evolution have come from studies in model plant and crop species ( Ding et al, 2018 ; Guarino et al, 2022 ; Varotto et al, 2022 ) which is primarily due to the availability of large genomic resources accumulated in this group of plants. The advancement in sequencing technologies and their cost effectiveness, has lately facilitated the availability of genomic resources in natural populations of non-model species as well.…”
Section: Epigenetic Variability Generates Phenotypic Plasticity Leadi...mentioning
confidence: 99%
“…The epialleles, also known as epigenetic alleles, are the loci having epigenetic modifications that may arise naturally or be induced artificially and are transferred stably to the next generation ( Taudt et al, 2016 ). In addition to natural genetic variation, which contributes to phenotypic diversity, epialleles impart an additional source of heritable variation ( Varotto et al, 2022 ; Figure 2 ). There are two ways in which epialleles could be formed: non-genetic (also known as epigenetic) and genetic ( Taudt et al, 2016 ).…”
Section: Plant Epibreedingmentioning
confidence: 99%
“…Furthermore, genetic epialleles arise due to the insertion of a transposon in an intergenic region, leading to its inactivation primarily by methylation of DNA ( Pecinka et al, 2013 ). The methylated DNA enhances methylation on all sides of the insertion site, leading to the formation of new epialleles ( Varotto et al, 2022 ). It has been documented in Arabidopsis, rice and maize ( Banks et al, 1988 ; Schmitz et al, 2013 ; Zhang et al, 2015 ).…”
Section: Plant Epibreedingmentioning
confidence: 99%